Regulatory T cells inhibit Fas ligand-induced innate and adaptive tumour immunity. - Simon, A; Jones, E; Richards, H; Wright, K; Betts, G; Godkin, A; Screaton, G; Gallimore, A (2007)
CD4+CD25+ regulatory T cells (Treg) are known to influence T cell responses to tumours. Here we have explored the role of Treg in inhibiting not only adaptive, but also innate immune responses to tumours. To this end we used a Fas ligand (FasL)-expressing melanoma cell line in a mouse model. In this system, innate immunity is sufficient to reject the tumour. All mice depleted of Treg and challenged with FasL-expressing melanoma remained tumour-free. Investigation of the underlying cellular effector mechanisms revealed that depletion of Treg enhanced an NK cell response capable of tumour lysis. Furthermore, this initial innate immune response primed mice to make an effective adaptive immune response leading to complete rejection of challenge with the parental melanoma. Both antigen-specific antibody and CD4+ T cells were implicated in protection via adaptive immunity. We conclude that removal of Treg and vaccination with whole tumour cells expressing FasL activates multiple arms of the immune system, leading to efficient tumour rejection. These findings highlight a novel role for FasL in inducing innate immune responses that are normally inhibited by Treg and uncover an adjuvant effect of FasL that can be used to stimulate tumour immunity after depletion of Treg.